(untitled) - Warhus, Susan P.; Susan Warhus (New York, 2007)
Written by a board-certified obstetrician and gynecologist, Fertility Demystified begins with an overview of the different fertility concerns for men and women along with a discussion of the possible reasons for early pregnancy loss. You'll find methods for increasing the chances of becoming pregnant--both naturally and through fertility drug therapy--and explanations of the various assisted-reproduction technologies. Also, the complex emotional issues and ethical considerations in the decision-making process are carefully explored
Includes bibliographical references (p. 243-249) and index
Keywords: Fertility; Human; Infertility; Infertility